A festa do bom Jesus dos navegantes em propriá-se: história de fé, espaço das relações sociais e laços culturais - Britto, Adelina Amélia Vieira Lubambo de (2010)
The study is a survey conducted for the Master of Social Sciences carried out in partnership between the Universidade Tiradentes-UNIT/SE and the Universidade Federal do Rio Grande do Norte (UFRN). Being a religious event, we seek to show that the religious parties generally have particular meanings for each nation or region. Amaral (1998) informs that the Brazilian parties regardless of where they occur are popular demonstrations that, as the context in which they present themselves, can dilute to crystallize, to celebrate, to ritualize or sacralize the particular social experience of the groups that do. They happen as a way to thank victories or important religious passages as Christmas, the June saints celebration, patron saints and patron saints considered. Thus, The Bom Jesus dos Navegantes party in Propriá-SE: story of faith, a space of social relations and cultural ties, is presented as our field of study because it is one of those celebrations that while celebrated in Sergipe, always on Sundays in January, by some municipalities situated along the river San Francisco, has the characteristic of overlap any others placed in town, including the one of the city's patron saint, Saint Anthony, held on June 13. Concerning the materials and methods, we opted for qualitative research and participant direct observation, using the techniques of personal notes, interviews, newspapers, websites, photos, videos and testimonials from participants and organizers, as well as references offered by experts of the area. With this research answers were sought to questions about what could keep alive the celebration of Bom Jesus dos Navegantes each year in order that this is a patron saint, not saint; the way as the investment of local government with more resources in this period, during the organization of arts festivals, has created a thread of tension with the Catholic Church promoting the religious rituals was reviewed. It was also analyzed how the sacred and profane spaces present themselves inseparable from the celebration and, finally, it was revealed that the party retains its value by preserving its tradition and making room for modernity, not weakening but suffering metamorphoses of time and space and can be seen in the social and cultural bonds wrapped by the time of religious faith